Does the “Weekend Effect” Extend to Friday Admissions? An Analysis of Ischemic Stroke Hospitalizations in South Carolina - Chen, Laite; Shi, Lu; Zhang, Donglan; Jiang, Chenyang; Truong, Khoa (Frontiers in Neurology, 2020)
Background. Weekend admission has been found to be associated with higher hospital mortality and longer hospital stay among patients with acute cardiovascular conditions. Whether those admitted on Fridays face similar risk as those admitted on Sundays and Saturdays remain uncertain. Methods. This study used 2012-2013 data from hospital records for nonfatal patients with ischemic stroke in the state of South Carolina. The database contained the universe of all hospitalizations in South Carolina except military and federal institutions. Multi-level logistic and linear regression models were performed to explore the temporal pattern for three outcomes: discharge to hospice, length of stay, and total charge by specific day in a week. Each model controlled for the patient age, gender, race /ethnicity, year of hospital admission, season of admission, payer, and Charlson Comorbidity Index. Results. A total of 19,346 nonfatal stroke hospitalizations were identified. Multilevel logistic regression shows that ischemic stroke patients admitted on non-Friday weekdays had a significantly lower odds of being discharged to hospice as compared with those admitted on Fridays (Odds Ratio: 0.80, 95% Confidence Interval: [0.65,0.99]) where there were not significant difference between Friday admissions and weekend admissions. The length of hospital stay admitted on non-Friday weekdays was significantly shorter than that of Friday admissions (IRR= 0.87, 95% CI: [0.84, 0.90]) whereas longer length of hospital stay was found on weekends admission (IRR= 1.06, 95% CI: [1.02, 1.11]). Friday admissions were not associated with higher charges as compared with non-Friday weekday admissions. Conclusions. Some hospitalization outcomes admitted on Fridays seemed to have the “weekend effects” too. Further studies are warranted to understand underlying mechanism for such a difference in outcomes between Friday and other weekdays. Interventions to close the weekend-weekday gap of patient outcomes need to consider the elevated risk on Fridays’ admission.